The Role of Shadow Teachers in Assisting Inclusive Students at SMA Negeri 10 Surabaya - Azzahra, Rahmadita Maulana (Jurnal Paradigma, 2026)
This study aims to describe the role and strategies of shadow teachers in supporting the learning process of students with special needs at SMA Negeri 10 Surabaya, an inclusive school. The presence of shadow teachers plays a crucial role in helping students understand subject matter, adapting learning media, and providing social and emotional support so that students can adapt to the regular learning environment. This study used descriptive qualitative methods through observation, interviews, and documentation studies of shadow teachers and inclusive students. The results show that shadow teachers play a strategic role as facilitators, motivators, and mediators between teachers, students, and parents. They implement personal and flexible mentoring strategies, including adjusting learning methods, strengthening character, and collaborating with subject teachers. However, challenges were also identified, including a lack of understanding of the role of shadow teachers and additional workloads. Therefore, competency improvement and collaboration between school stakeholders are needed to strengthen the implementation of inclusive education sustainably.